THE EFFECT OF CONVECTIVE FIXED BED DRYING BASED ON A SOLAR COLLECTOR AND PHOTOVOLTAIC (CSD) TO THE QUALITY ATRIBUTES OF RED PEPPER COMPARED WITH CONVENTIONAL CONVECTIVE FIXED BED DRYING (CCD) - Siti Asmaniyah Mardiyani; Sumardi Hadi Sumarlan; Bambang Dwi Argo; Amin Setyo Leksono (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2019)
The effect of conventional convective drying (CCD) and convective solar drying (CSD) based on a solar collector and photovoltaic on the quality of dried red pepper was researched. The study was aimed to determine the effect of five drying system (CCD 50°C, CCD 60°C, CCD 70°C, CSD, and open sun drying) on the quality attributes of dried red pepper. The quality observed were rehydration ratio, ascorbic acid, capsaicin, non-enzymatic browning index, anthocyanin, and carotenoids. The results of the study confirmed that the drying system significantly affected the quality attributes of dried red pepper except for anthocyanin. The CSD had a satisfactory result, shown by some attributes (carotenoids, ascorbic acid, and ratio) which were not statistically different from the quality of dried red pepper gained from CCD 50°C.